2017
DOI: 10.1007/s00068-017-0822-6
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage treatment in patients with patients with high-energy femoral fractures does not lead to an increase in deep infectious complications: a propensity score analysis

Abstract: PurposeIn patients following severe trauma sometimes the physiological condition or soft tissue status may not allow definitive fixation of a femoral fracture. In these patients, an external fixator can be placed to temporarily stabilise the fracture, after which definitive fixation can be performed in a second procedure. The aim of this study was to compare the postoperative wound infection and union rates of patients treated with direct intramedullary nailing (IMN) and patients treated with the ‘two-stage tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The major challenge and drawback of non-surgical management is the unequal length of lower limbs in our setting. It is the most common complication of femoral shaft fractures in children, mainly manifested as overgrowth [29]. Most of these cases develop limb length discrepancy in the first two years after the fracture, especially in the first three months; subsequently, it tends to disappear gradually within two years after the fracture.…”
Section: Discussionmentioning
confidence: 99%
“…The major challenge and drawback of non-surgical management is the unequal length of lower limbs in our setting. It is the most common complication of femoral shaft fractures in children, mainly manifested as overgrowth [29]. Most of these cases develop limb length discrepancy in the first two years after the fracture, especially in the first three months; subsequently, it tends to disappear gradually within two years after the fracture.…”
Section: Discussionmentioning
confidence: 99%
“…The injury mechanism (high energy) has been verified as an independent risk factor of SSI [ 48 ], which was reconfirmed in the present study. First, the high-energy injuries meant the resultant more damaged skin, the fractured bone itself, and even open wounds, which allowed microbial easy to colonize and contaminate to give rise to SSI [ 43 , 49 ]. Moreover, our data showed that the operative time in the high-energy group was approximately twice that of the low-energy group, which might have prolonged the exposure of wounds to the air, resulting in the increased risk of infection [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients with severe soft tissue injuries (Gustilo III) were not indicated for intramedullary nailing due to a high risk of infection [ 11 , 12 ]. For high-energy hip trauma, Dingemans et al [ 32 ] compared direct intramedullary nailing and two-stage treatment, concluding that two-stage treatment is a safe treatment option in young patients in terms of post-surgery wound infections and union rates. Our results are similar and support this opinion.…”
Section: Discussionmentioning
confidence: 99%